Polymorphism of the T4842G Myostatin Gene is Associated with Carcass Characteristics in Indonesian Chickens - Khaerunnisa, Isyana; Pramujo, Muhammad; Arief, Irma Isnafia; Budiman, Cahyo; Gunawan, Asep; Jakaria; Sumantri , Cece (International Journal of Poultry Science, 2016)
Myostatin, or growth and differentiation factor-8 (GDF-8), is a member of the Transforming Growth Factor (TGF)-β superfamily. This family functions as a negative regulator of skeletal muscle. Mutations in exon 2 have been reported to convert Thymine into Guanine (T4842G) that alters the amino acid leucine into arginine, which is associated with body weight in chickens. The objectives of this study were to identify the polymorphism of T4842G mutation in the myostatin gene in Indonesian chickens and evaluate their effects on carcass characteristics. The gene polymorphism was identified with the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method using the BsrI restriction enzyme. The effect of genotype on carcass and meat quality was analyzed using the SAS General Linear Model (GLM) procedure. Genotyping was performed on 332 chickens from 7 Indonesian chicken populations (Kampung, Merawang, Sentul, Cobb broiler, F1 crossbreed of Kampung x layer, F1 crossbreed of Kampung x Cobb broiler and F2 crossbreed of Kampung x Cobb broiler). The product of amplification was 247 bp. The myostatin|BsrI locus was polymorphic in all populations, producing two alleles (G and T) and three genotypes (GG, GT, TT). Results from the analysis of the allele and genotype frequency showed that the T allele had a higher frequency than the G allele in all populations, except for the F1 crossbreed of the Kampung x Cobb broiler chicken population, which had equal allele frequencies. A significant effect was found between genotype and carcass characteristics in the F2 crossbreed Kampung x Cobb broiler chickens. A SNP in the coding region of myostatin in exon 2 was associated with live weight, carcass weight, breast weight, thighs weight, drum sticks weight, wings weight, breast muscle weight, thighs muscle weight, drum sticks muscle weight and free water. Here, the association of myostatin|BsrI gene polymorphism with chicken carcass characteristics in Indonesian chickens has been demonstrated, providing evidence that myostatin might be an important candidate gene for chicken carcass characteristics.